KUALITAS TIDUR PASIEN CONGESTIVE HEART FAILURE (CHF) PADA POSISI TIDUR MIRING KEKANAN - Suci Khasanah; Harnanto Setyo Pambudi (Viva Medika, 2014)
A series of studies shows the influence of sleep on quality of sleep position. Setting theposition of sleep is one of the nursing actions that aim to reduce breathlessness and meetpatient needs rest so as to obtain good quality sleep. This study aims to determine the qualityof sleep in a sleeping position facing to the right in congestive heart failure patients.Comparative descriptive study with a population of congestive heart failure patients withoutCOPD. The sample size of 16 respondents consecutive sampling and sampling techniques.The instrument used was obserbvasi sheet and a video recorder as well as kuasioner ThePittsburgh Sleep QualityIndex (PSQI). The results of measuring the quality of sleep in anumeric scale and analysis of different test used is Independent sample t test. The resultsshowed a mean score of sleep quality treatment groups smaller than the control group(respectively 6.75 and 10.5). Results obtained independent t-test p 0.015 <Î±. Conclusion: Nodifference in sleep quality scores between the treatment group and the control group,statistically significant. Thus, the quality of sleep of heart failure patients were skewed rightkongstif better than sleeping position facing in addition to the right. Keywords: Quality, Sleep Position, Congestive Heart Failure